Channels of international risk-sharing: capital gains versus income flows - Thierry Bracke; Martin Schmitz (European Central Bank (ECB), 2008)
Global financial integration unlocks a huge potential for international risk sharing. We examine the degree to which international equity holdings act as a risk sharing device in industrial and emerging economies. We split equity returns into investment income (dividend distribution) and capital gains to investigate which of the two channels delivers the largest potential for risk sharing. Our evidence suggests that net capital gains are a more potent channel of risk sharing. They behave in a countercyclical way, that is they tend to be positive (negative) when the domestic economy is growing more slowly (rapidly) than the rest of the world. Countries with more countercyclical net capital gains experience improved consumption risk sharing. The empirical analysis furthermore suggests that these risk sharing properties of net capital gains have increased through time, in particular in the 1990s and early-2000s, on the back of a declining equity home bias and financial market deepening.
Keywords: F21; F30; F36; 330; consumption smoothing; Cross-Border Investment; International portfolio diversification; International risk sharing; Valuation effects; Internationaler Finanzmarkt; Kapitalmobilität; Portfolio-Management; Anlageverhalten; Welt